A dual-enzyme cleavable linker for antibody–drug conjugates. Issue 28 (9th March 2021) - Bargh, Jonathan D.; Walsh, Stephen J.; Ashman, Nicola; Isidro-Llobet, Albert; Carroll, Jason S.; Spring, David R.
Abstract : A 3- O -sulfo-β-galactose linker is cleaved by two lysosomal enzymes to release payloads from ADCs at targeted cancer cells. Abstract : A novel enzyme cleavable linker for antibody–drug conjugates is reported. The 3- O -sulfo-β-galactose linker is cleaved sequentially by two lysosomal enzymes – arylsulfatase A and β-galactosidase – to release the payload in targeted cells. An α-HER2 antibody–drug conjugate synthesised using this highly hydrophilic dual-cleavable linker exhibited excellent cytotoxicity and selectivity.